Alteration of fatty acid chain length of Chlamydomonas reinhardtii by simultaneous expression of medium‐chain‐specific thioesterase and acyl carrier protein. Issue 1 (January 2017) - Inaba, Yu; Nakahigashi, Kenji; Ito, Takuro; Tomita, Masaru
SUMMARY: Biofuel from fatty acids with chain lengths of 8–15 (C8–C15) have properties similar to those of conventional diesel and jet fuels, thus, can save time and reduce costs for the refurbishment of engines and maintenance of oiling facilities. Most oil‐producing algae yield C16–C18 fatty acids; however, the manipulation of algae using genetic engineering is a promising approach to obtain C8–C15 fatty acids. The introduction of a medium‐chain‐specific thioesterase (TE) is expected to effectively alter algae to produce medium‐chain fatty acids (MCFAs). TE is the main determinant of fatty acid chain length as it releases fatty acids from the acyl carrier protein (ACP) in the fatty acid elongation cycle. In a previous study, the introduction of heterologous C8–C12‐specific TEs into Chlamydomonas reinhardtii did not increase the yield of MCFAs. This effect was attributed to a low affinity of the heterologous TEs to C. reinhardtii ACP. Therefore, we introduced both the C10–C14‐specific TE gene and the ACP gene from the land plant Cuphea lanceolata into C. reinhardtii . We measured free fatty acids (FFAs) and triacylglycerols (TAGs) in the transformants using liquid chromatography–mass spectrometry. The production of C12:0 and C14:0, chain length 12 and 14 without unsaturation, FFAs was not significantly increased in any of the tested strains. However, we found a slight but significant increase in TAG‐containing MCFAs in both TE only and TE–ACP transformants. The increased production rate of C14:0‐containing TAGs ranged from 1.25‐ to 1.58‐fold, indicating the ability of medium‐chain‐specific TE to increase MCFAs. These results suggest that the selection of specific TEs is important when modifying eukaryotic algae to produce MCFAs.